Sex-Biased Transcriptome of Schistosoma mansoni: Host-Parasite Interaction, Genetic Determinants and Epigenetic Regulators Are Associated with Sexual Differentiation. - Marion A L Picard; Jérôme Boissier; David Roquis; Christoph Grunau; Jean-François Allienne; David Duval; Eve Toulza; Nathalie Arancibia; Conor R Caffrey; Thavy Long; Sabine Nidelet; Marine Rohmer; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Among more than 20,000 species of hermaphroditic trematodes, Schistosomatidae are unusual since they have evolved gonochorism. In schistosomes, sex is determined by a female heterogametic system, but phenotypic sexual dimorphism appears only after infection of the vertebrate definitive host. The completion of gonad maturation occurs even later, after pairing. To date, the molecular mechanisms that trigger the sexual differentiation in these species remain unknown, and in vivo studies on the developing schistosomulum stages are lacking. To study the molecular basis of sex determination and sexual differentiation in schistosomes, we investigated the whole transcriptome of the human parasite Schistosoma mansoni in a stage- and sex-comparative manner. METHODOLOGY/ PRINCIPAL FINDINGS:We performed a RNA-seq on males and females for five developmental stages: cercariae larvae, three in vivo schistosomulum stages and adults. We detected 7,168 genes differentially expressed between sexes in at least one of the developmental stages, and 4,065 of them were functionally annotated. Transcriptome data were completed with H3K27me3 histone modification analysis using ChIP-Seq before (in cercariae) and after (in adults) the phenotypic sexual dimorphism appearance. In this paper we present (i) candidate determinants of the sexual differentiation, (ii) sex-biased players of the interaction with the vertebrate host, and (iii) different dynamic of the H3K27me3 histone mark between sexes as an illustration of sex-biased epigenetic landscapes. CONCLUSIONS/ SIGNIFICANCE:Our work presents evidence that sexual differentiation in S. mansoni is accompanied by distinct male and female transcriptional landscapes of known players of the host-parasite crosstalk, genetic determinants and epigenetic regulators. Our results suggest that such combination could lead to the optimized sexual dimorphism of this parasitic species. As S. mansoni is pathogenic for humans, this study represents a promising source of therapeutic targets, providing not only data on the parasite development in interaction with its vertebrate host, but also new insights on its reproductive function.